Manajemen Ekstrakurikuler Robotika dalam Peningkatan Prestasi Non Akademik Siswa di MTsN 13 Jombang - Lasmana, Triman Indra; Hakim, Lukman (YASIN, 2025)
The limited number of studies on robotics extracurricular management in madrasahs serves as the background of this research, despite the significant impact such activities have on enhancing students’ non-academic achievements. This study aims to examine the management of robotics extracurricular programs in supporting non-academic performance at MTsN 13 Jombang. A qualitative approach with a case study design was employed, involving research subjects including the principal, vice principal for student affairs, the robotics extracurricular coordinator, and students, selected through purposive sampling. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that robotics extracurricular management at MTsN 13 Jombang is carried out systematically through the stages of planning, implementation, and evaluation. The program begins with student recruitment, internal competitions, and regular training held every Friday, with intensified sessions prior to competitions. Evaluation is conducted in two phases, before and after the competitions to identify weaknesses that require improvement. Challenges encountered include limited facilities and constrained training time. The study concludes that well-structured extracurricular management plays a crucial role in developing students’ interests, talents, and skills, thereby enhancing non-academic achievement. The implications involve strengthening the managerial capacity of madrasahs and offering practical recommendations to extracurricular coordinators for improving the effectiveness and sustainability of robotics programs.